Mechanisms of Flavor Substance Formation in Pengqi Sauce Based On an Integrated Analysis of Absolute Microbial Quantification and Volatomics - Xiaojie Hou; Hongmei Yin; Xiaodie Qin; Jingjing Zhang; Yangyang Wang; Weiming Su; Hui Cao; Hui Wang (Food Frontiers, 2025)
ABSTRACT Pengqi sauce is a traditional Chinese naturally fermented aquatic product, and its unique flavor formation mechanism is closely related to microbial function. In this study, we combined metabolomics and microbiomics techniques to analyze the flavor evolution and the rules and mechanisms of bacterial flora action during the natural fermentation process of Wedelia sauce. On the basis of electronic nose, gas chromatography–mass spectrometry (GC–MS) and GC–ion mobility spectrometry (GC–IMS) techniques, nine core flavor components, including 2‐methylpyrazine, 1‐heptanol, tetrahydrothiophene, and isoamyl isobutyrate, which confer baking, fruity, and creamy aromas, were identified as key volatile components during the fermentation process. Meanwhile, the 16S rRNA sequencing technology was used for the first time to clarify the flavor profile of the Pengqi sauce fermentation system. The actual abundance changes of microorganisms in the Pengqi sauce fermentation system: Paracoccus, Nocardioides, and Marinilactibacillus, the absolute abundance of which reached 12,129, 9411, and 9113 copies/g, respectively, on Day 56, and still maintained a high level on Day 84. Orthogonal partial least squares discriminant analysis (OPLS‐DA) and Spearman correlation analyses indicated that the above genera showed very strong positive correlations (ρ > 0.9, p < 0.05) with key flavor substances such as 1‐hexanol and 2‐methylpyrazine, and their functional predictions indicated that they drove flavor formation through protein degradation, lipid oxidation, and glucose metabolism pathways. This study demonstrated that the absolute microbial quantification strategy can reveal the contribution of bacterial flora to fermentation flavor more accurately and provide a theoretical basis for process optimization and standardized production of traditional fermented foods.